“Scoutlink” Digital English Book for Indonesian Scouting - Yulia Savhika S.; Masruddin; Jufriadi (Universitas Islam Negeri Palopo, 2025)
This study aims to develop and evaluate Scoutlink, a barcode-based digital English book designed to support English vocabulary learning for Indonesian Scout members. The research was conducted due to the limited availability of contextual English learning resources that accommodate the needs of Scout members who increasingly participate in national and international scouting activities. This study employed a Research and Development (R&D) approach using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The participants were 25 active Scout members from 15 regions in Indonesia, selected through random sampling. Data were collected through needs analysis questionnaires, expert validation instruments, and product effectiveness tests. The results of the needs analysis indicate that 100% of respondents stated that the development of Scoutlink is highly necessary to support English vocabulary mastery related to scouting activities. In addition, 96% of respondents agreed that barcode-based access facilitates flexible and practical learning, while 92% expected the product to reflect scouting identity through its design. Expert validation results demonstrate that Scoutlink achieved a very high level of validity in material, design, curriculum, and language aspects. Furthermore, the effectiveness test shows that the use of Scoutlink improves users’ understanding of English vocabulary in scouting contexts, categorizing the product as highly effective. Therefore, Scoutlink is considered a valid, practical, and effective digital learning medium to support English vocabulary learning in non-formal education settings.